Postoperative Pain after Root Canal Treatment: A Prospective Cohort Study - M. Gotler; B. Bar-Gil; M. Ashkenazi (Hindawi Limited, 2012)
Aim. To evaluate the incidence and severity of postendodontic treatment pain (PEP) subsequent to root canal treatment (RCT) in vital and necrotic pulps and after retreatment. Methodology. A prospective study. Participants were all patients (𝑛=274) who underwent RCT in teeth with vital pulp, necrotic pulp, or vital pulp that had been treated for symptomatic irreversible pulpitis or who received root canal retreatment, by one clinician, during an eight-month period. Exclusion criteria were swelling, purulence, and antibiotic use during initial treatment. A structured questionnaire accessed age, gender, tooth location, and pulpal diagnosis. Within 24 h of treatment, patients were asked to grade their pain at 6 and 18 hours posttreatment, using a 1-5 point scale. Results. RCT of teeth with vital pulp induced a significantly higher incidence and severity of PEP (63.8%; 2.46 ± 1.4, resp.) than RCT of teeth with necrotic pulp (38.5%; 1.78 ± 1.2, resp.) or of retreated teeth (48.8%; 1.89 ± 1.1, resp.). No statistical relation was found between type of pain (spontaneous or stimulated) and pulp condition. Conclusion. RCT of teeth with vital pulp induced a significantly higher incidence and intensity of PEP compared to teeth with necrotic pulp or retreated teeth.